Blocked by caste : economic discrimination in modern India - Thorat, Sukhadeo; Newman, Katherine S., 1953- (New Delhi : Oxford University Press, 2010)
Contributed articles.
Includes bibliographical references (p. [368]-374).
Keywords: Caste -- Economic aspects -- India; Discrimination -- Economic aspects -- India; Marginality, Social -- Economic aspects -- India